INTERPRETASI TRADISI MAARAK BUNGO LAMANG DISOLOK SELATAN DALAM KARYA TARI KONTEMPORER SASURAMBI - Dendi chairi; Susas Rita Loravianti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The Maarak Bungo Lamang tradition in South Solok Regency, the main focus of this study, is a cultural practice that blends religious and aesthetic elements in the celebration of the Prophet Muhammad’s Birthday (Maulid Nabi). This tradition features the making of lamang decorated with paper flowers, miniatures, and colorful ornaments, accompanied by the badikia chant performed with rebana drums. Its visual uniqueness and embedded spirituality serve as the foundation for the creation of a contemporary dance work titled “Sasurambi.” The purpose of this research is to interpret the symbolic meanings, social values, and religious messages within the Maarak Bungo Lamang tradition and to translate them into a contemporary dance composition. The study employs a Research and Development (R&D) method using a deconstructive approach, which dismantles the structure of the tradition to reveal layers of meaning behind its visual and musical elements. The theoretical framework includes Derrida’s theory of deconstruction as a basis for re-reading the tradition, aesthetic theory for analyzing its visual and artistic components, and cultural anthropology for examining its social functions in the South Solok community.The findings indicate that Maarak Bungo Lamang embodies religious values expressed as love for the Prophet Muhammad, aesthetic values through its vibrant colors and forms, and social values manifested in communal cooperation. These values are transformed into movement motifs, group dynamics, and dramaturgical structure in the dance work Sasurambi. In conclusion, interpreting the tradition through deconstruction enables the creation of a contemporary dance piece that not only re-presents the tradition but also serves as a medium for preserving local culture in a form adaptable to modern performing arts.